Influence of modulated signals at the hydrocarbon deposit - E. Y. Zayats; V. F. Yanushkevich; S. V. Kalintsev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of studies of the interaction modulated signals with different parameters with hydrocarbon deposits was carried out.